2012
DOI: 10.1186/2045-9912-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Drinking hydrogen water and intermittent hydrogen gas exposure, but not lactulose or continuous hydrogen gas exposure, prevent 6-hydorxydopamine-induced Parkinson’s disease in rats

Abstract: BackgroundLactulose is a synthetic disaccharide that can be catalyzed only by intestinal bacteria in humans and rodents, and a large amount of hydrogen is produced by bacterial catalysis of lactulose. We previously reported marked effects of ad libitum administration of hydrogen water on prevention of a rat model of Parkinson’s disease (PD).MethodsEnd-alveolar breath hydrogen concentrations were measured in 28 healthy subjects and 37 PD patients, as well as in 9 rats after taking hydrogen water or lactulose. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 23 publications
3
83
0
Order By: Relevance
“…Asterisks indicate statistical significance as determined by Student's t test (*p \ 0.05) for D, E, F, and one-way ANOVA and Tukey's multiple-comparison test (***p \ 0.001) for H stronger effect than administration of either alone. We previously showed that HRW, but not HCA, was effective in a Parkinson's disease rat model; however, by inducing a blood concentration of H 2 similar to that produced by HRW, intermittent administration of HCA resulted in intermediate effects between HRW and the normal HCA treatment [12]. This result suggests that H 2 bioactivity depends not only on its blood concentration but also on changes in the H 2 Fig.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Asterisks indicate statistical significance as determined by Student's t test (*p \ 0.05) for D, E, F, and one-way ANOVA and Tukey's multiple-comparison test (***p \ 0.001) for H stronger effect than administration of either alone. We previously showed that HRW, but not HCA, was effective in a Parkinson's disease rat model; however, by inducing a blood concentration of H 2 similar to that produced by HRW, intermittent administration of HCA resulted in intermediate effects between HRW and the normal HCA treatment [12]. This result suggests that H 2 bioactivity depends not only on its blood concentration but also on changes in the H 2 Fig.…”
Section: Discussionmentioning
confidence: 83%
“…We have previously investigated the differences between HRW and HCA using Parkinson's disease model rats [12]; however, neither other report has compared the therapeutic effects between HRW and HCA nor demonstrated their different molecular actions. To explore this, we selected nine genes from Supplementary Fig.…”
Section: Hrw and Hca Additively Alter Gene Expression In Liver And Otmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen-saturated water (1.6 ppm or 0.8 mM) was prepared daily, using an AquelaBlue electrolysis instrument (Miz Co Ltd, Fujisawa, Japan). 11 Rats were housed ad libitum to food and water, including hydrogen-saturated water in group H, under a natural day/night cycle. Rats were acclimated for 7 days before any experimental procedures were conducted.…”
Section: Methods Animal Modelsmentioning
confidence: 99%
“…Hydrogen gas (H 2 ) was recently revealed as a signaling modulator with multiple biological functions in clinical trails (Ohsawa et al, 2007;Itoh et al, 2009;Ito et al, 2012). It was previously found that a hydrogenase system could generate H 2 in bacteria and green algae (Meyer, 2007;Esquível et al, 2011).…”
mentioning
confidence: 99%